A graphene-like N-annulated perylene diimide dimer compound for highly efficient electrochemiluminescence. (10th May 2023) - Qin, Xiaoli; Yang, Liuqing; Zhan, Ziying; Cieplechowicz, Edward; Chu, Kenneth; Zhang, Congyang; Jahanghiri, Sara; Welch, Gregory C.; Ding, Zhifeng
Highlights: Relative and absolute electrochemiluminescence (ECL) efficiencies were determined. N-annulated PDI compound tPDI2 N-TMB was explored for ECL efficiency and mechanisms. ECL in both annihilation and coreactant pathways were investigated. ECL-voltage curves with corresponding spooling ECL spectra reveal ECL mechanisms. tPDI2 N-TMB has great potential in LED and bioanalytical applications. Abstract: Perylene diimide (PDI) derivatives, as important optoelectronically active materials, have been explored for the development of high-performance organic light-emitting diodes, fluorescent and electrochemiluminescent (ECL) luminophores. Herein, the ECL performance and its absolute efficiency of a graphene-like N-annulated PDI derivative, tPDI2 N-trimethylbenzyl (tPDI2 N-TMB) in annihilation route and coreactant pathways with tri- n -propylamine (TPrA) and benzoyl peroxide (BPO) are investigated. The ECL-voltage curves with corresponding spooling ECL spectra demonstrate the light generation mechanisms. ECL emission peak wavelengths of tPDI2 N-TMB at 675 nm in these systems are similar to its photoluminescence (PL) one, proving that ECL emissions from tPDI2 N-TMB with TPrA or BPO coreactant system are mainly from the monomeric excited states without surface states and the dimerization processes as in the case of graphene quantum dots. The relative ECL efficiency of the tPDI2 N-TMB/TPrA system was determined to be 165%, which is higher than those of many organic molecules. Considering the difference in radical behaviors between tPDI2 N-TMB and Ru(bpy)3 2+, absolute ECL efficiencies are suitable to reflect the electrochemical and ECL processes objectively. The excellent ECL performance of tPDI2 N-TMB reveals great potentials for the development of new PDI compounds in light emitting devices and bioanalytical applications. Graphical abstract: Image, graphical abstract